Simulasi Direct Sequence Spread Spectrum (DSSS) Pada Modulasi Binary Phase Shift Keying (BPSK) - Nabila Khansa Hartono; Faradila Alvina Putri; Fitri Elvira Ananda (Politeknik Negeri Jakarta, 2021)
Spread spectrum is a data transmission technique that spreads out information spectrum energy signals in a frequency band that is much larger than the minimal spectrum. One of the spread spectrum techniques is Direct Sequence Spread Spectrum (DSSS). This research was built the simulation of DSSS on Binary Phase Shift Keying (BPSK) modulation using MATLAB software. The simulation results of this DSSS simulation are displaying information wave signals, PN codes, signals that have been added with PN codes, signals modulated with BPSK, modulation signals that have been added with AWGN noise, demodulation signals, DSSS output signals and BER vs SNR graphics on the channel AWGN. The simulator of DSSS on BPKS in this research have been running according to the DSSS signal order flow and theoretical concept. Keywords: AWGN, BPSK , DSSS, PN Code, PN Sequence